Low X-ray surface brightness clusters: implications on the scatter of the M–T and L–T relations. Issue 4 (3rd February 2022) - Andreon, S; Trinchieri, G; Moretti, A
ABSTRACT: We aim at studying scaling relations of a small but well-defined sample of galaxy clusters that includes the recently discovered class of objects that are X-ray faint for their mass. These clusters have an average low X-ray surface brightness, a low gas fraction, and are underrepresented (by a factor of 10) in X-ray surveys or entirely absent in Sunyaev-Zeldovich (SZ) surveys. With the inclusion of these objects, we find that the temperature–mass relation has an unprecedentedly large scatter, 0.20 ± 0.03 dex at fixed mass, as wide as allowed by the temperature range, and the location of a cluster in this plane depends on its surface brightness. Clusters obey a relatively tight luminosity–temperature relation independently of their brightness. We interpret the wide difference in scatter around the two relations as due to the fact that X-ray luminosity and temperature are dominated by photons coming from small radii (in particular for T we used a 300 kpc aperture radius) and strongly affected by gas thermodynamics (e.g. shocks and cool cores), whereas mass is dominated by dark matter at large radii. We measure a slope of 2.0 ± 0.2 for the L 500 –T relation. Given the characteristics of our sample, this value is free from collinearity (degeneracy) between evolution and slope and from hypothesis on the undetected population, which both affect the analysis of X-ray-selected samples, and can therefore be profitably used both as reference and to break the aforementioned degeneracy of X-ray-selected samples.